Combined Therapy With Avastin, a PAF Receptor Antagonist and a Lipid Mediator Inhibited Glioblastoma Tumor Growth - Cruz Flores, Valerie A.; Menghani, Hemant; Mukherjee, Pranab K.; Marrero, Luis; Obenaus, Andre; Dang, Quan; Khoutorova, Larissa; Reid, Madigan M.; Belayev, Ludmila; Bazan, Nicolas G. (Frontiers in Pharmacology, 2021)
Glioblastoma multiforme (GBM) is an aggressive, highly proliferative, invasive brain tumor with a poor prognosis and low survival rate. The current standard of care for GBM is chemotherapy combined with radiation following surgical intervention, altogether with limited efficacy, since survival averages 18 months. Improvement in treatment outcomes for patients with GBM requires a multifaceted approach due to the dysregulation of numerous signaling pathways. Recently emerging therapies to precisely modulate tumor angiogenesis, inflammation, and oxidative stress are gaining attention as potential options to combat GBM. Using a mouse model of GBM, this study aims to investigate Avastin (suppressor of vascular endothelial growth factor and anti-angiogenetic treatment), LAU-0901 (a platelet-activating factor receptor antagonist that blocks pro-inflammatory signaling), Elovanoid (ELV; a novel lipid mediator that protects neural cell integrity), and their combination as an alternative treatment for GBM. Female athymic nude mice were anesthetized with ketamine/xylazine, and luciferase-modified U87MG tumor cells were stereotactically injected into the right striatum. On post-implantation day 13, mice received one of the following: LAU-0901, ELV, Avastin, and all three compounds in combination. Bioluminescent imaging (BLI) was performed on days 13, 20, and 30 post-implantation. Mice were perfused for ex vivo MRI on day 30. Bioluminescent intracranial tumor growth percentage was reduced by treatments with LAU-0901 (43%), Avastin (77%), or ELV (86%), individually, by day 30 compared to saline treatment. In combination, LAU-0901/Avastin, ELV/LAU-0901, or ELV/Avastin had a synergistic effect in decreasing tumor growth by 72%, 92%, and 96%, respectively. Additionally, tumor reduction was confirmed by MRI on day 30, which shows a decrease in tumor volume by treatments with LAU-0901 (37%), Avastin (67%), or ELV (81.5%), individually, by day 30 compared to saline treatment. In combination, LAU-0901/Avastin, ELV/LAU-0901, or ELV/Avastin had a synergistic effect in decreasing tumor growth by 69%, 78.7%, and 88.6%, respectively. We concluded that LAU-0901 and ELV combined with Avastin exert a better inhibitive effect in GBM progression than monotherapy. To our knowledge, this is the first study that demonstrates the efficacy of these novel therapeutic regimens in a model of GBM and may provide the basis for future therapeutics in GBM patients.